A negative MYB regulator of proanthocyanidin accumulation, identified through expression quantitative locus mapping in the grape berry. Issue 3 (21st October 2013) - Huang, Yung‐Fen; Vialet, Sandrine; Guiraud, Jean‐Luc; Torregrosa, Laurent; Bertrand, Yves; Cheynier, Véronique; This, Patrice; Terrier, Nancy
Summary Flavonoids are secondary metabolites with multiple functions. In grape (Vitis vinifera), the most abundant flavonoids are proanthocyanidins (PAs), major quality determinants for fruit and wine. However, knowledge about the regulation of PA composition is sparse. Thus, we aimed to identify novel genomic regions involved in this mechanism. Expression quantitative trait locus (eQTL) mapping was performed on the transcript abundance of five downstream PA synthesis genes (dihydroflavonol reductase (VvDFR), leucoanthocyanidin dioxygenase (VvLDOX), leucoanthocyanidin reductase (VvLAR1), VvLAR2 and anthocyanidin reductase (VvANR)) measured by real‐time quantitative PCR on a pseudo F1 population in two growing seasons. Twenty‐one eQTLs were identified; 17 of them did not overlap with known candidate transcription factors or cis‐regulatory sequences. These novel loci and the presence of digenic epistasis support the previous hypothesis of a polygenic regulatory mechanism for PA biosynthesis. In a genomic region co‐locating eQTLs for VvDFR, VvLDOX and VvLAR1, gene annotation and a transcriptomic survey suggested that VvMYBC2‐L1, a gene coding for an R2R3‐MYB protein, is involved in regulating PA synthesis. Phylogenetic analysis showed its high similarity to characterized negative MYB factors. Its spatiotemporal expression profile in grape coincided with PA synthesis. Its functional characterization via overexpression in grapevine hairy roots demonstrated its ability to reduce the amount of PA and to down‐regulate expression of PA genes.